Interacción: conciencia lingüística y desarrollo heteroglósico de los argumentos de refutación en el aula de E/LE - Calderón García, Chirley; Llanes Barbuzano, Rómula (Rastros Rostros, 2020)
The use of the language has three constituent elements: The place mat, the discursive and the ideological. The establishment of a complex dialogue through different levels of abstraction in two essential senses supports. The heteroglosy and the argumentation conjugate themselves to give a polyhedral, intertextuality and polyphonic perspective on the themes that are debated at the classroom, that will make possible than the speaker- interpret dialogue, argue, interpret, recreate the texts produced in a respectful and communicatively effective interchange with the other one. In this context, the study has the idea to research about heteroglossic characteristics of the arguments presents in the refutatory developments at the class of E/LE.
Keywords: heteroglosy; dialogue; refutation argument